Pengaruh Pijat Bayi Terhadap Kualitas Tidur Bayi Umur 0-6 Bulan Di Puskesmas Kartasura - Pamungkas, Bintang Aji, Endang Zulaicha Susilaningsih, S.Kp., M.Kep (2016)
Good night's sleep is essential for the growth of the baby, because the baby's brain during sleep growth peaked. But in fact in one study found 51.3% of infants experienced sleep disturbances, 42% infant nighttime sleep less than nine hours, and at night the baby wakes up more than 3 times with old woke up more than an hour. One non-pharmacologic therapy to overcome the problem of sleeping baby is a baby massage. This study aims to determine the effect of massage on babies with sleep quality infant aged 0-6 months in Puskesmas Kartasura. This research method is analytical use case control design. Collecting data using a questionnaire, while data analysis using Chi Square test. Chi Square test results obtained 2hitung value of 20.417 (p-value = 0.001) and the Value of odds ratios (OR) test of 15.00. The conclusion of the study there the effect of infant massage with sleep quality infant aged 0-6 months where infants who received infant massage likely to have a good sleep quality is 15 times higher than babies who do not get a baby massage.